1991
DOI: 10.1159/000116669
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Herpes Zoster Myelitis: Positive Magnetic Resonance Imaging Finding

Abstract: A 33-year-old man developed a progressive myelopathy after a characteristic skin lesion of herpes zoster involving the right C3 and C4 dermatomes. The lesions were recognizable in the T2-weighted image of the magnetic resonance imaging (MRI) as increased signal intensities throughout the long segments of the spinal cord with maximal in the cervical portion, which was compatible with the pathological findings reported in autopsy studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
1

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 10 publications
0
7
1
Order By: Relevance
“…In myelitis the detection of varicella zoster virus in CSF has been reported [18]. In other previously reported cases, there was no serological confirmation of HZV infection [21,33]. The spinal cord lesion in our case was on the same side and one segment above the initially affected segment where the vesicular eruptions were recognized.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…In myelitis the detection of varicella zoster virus in CSF has been reported [18]. In other previously reported cases, there was no serological confirmation of HZV infection [21,33]. The spinal cord lesion in our case was on the same side and one segment above the initially affected segment where the vesicular eruptions were recognized.…”
Section: Discussioncontrasting
confidence: 40%
“…Usually, the results of serological tests are not available in the early stages of the disease, causing diagnostic uncertainty with respect to aetiology [3,20,21,34]. In magnetic resonance imaging (MRI) of the spine, intravenous (i.v.)…”
Section: Introductionmentioning
confidence: 99%
“…In a detailed report that included post mortem examination of the spinal cord, Hogan et al [10] presented evidence of direct invasion of VZV in a patient with transverse myelitis associated with herpes zoster. Demonstration of the VZV antigen in CSF cells by immunofluorescence or isolation of VZV from the CSF is a confirmative evidence for viral central nervous system infection but it is rarely successful [11].…”
Section: Discussionmentioning
confidence: 99%
“…This process was disseminated throughout the spinal cord; the fact that the maximum number of lesions was at the T9-10 level was consistent with the clinical sensory level and the autopsy findings, perhaps reflecting the original level of VZV reactivation and entry into the spinal cord. In a recent report, an MRI study of a patient with VZV myelitis following herpes zoster involving the C3-4 dermatomes demonstrated an increased T2-weighted signal throughout the long segments of the spinal cord; the study revealed that the maximum number of lesions were in the cervical region, a finding consistent with those at autopsy [9]. In a retrospective review of this case, the sensory level in correlation with findings on the MRI scan might have been used to suggest the correct diagnosis.…”
mentioning
confidence: 54%